Risk management: the new normative scenario and the role of training and education - Ferrari, Antonio; Odone, Anna; Mandelli, Paolo; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2017)
The article focuses on the important issue of Risk Management in health. In particular, it describes and critically appraises the new Italian law on patients’ safety and professional responsibility, and expand on the educational and training needs to implement it on the ground. On the basis of the new law the role of Risk Managers, responsible for quality and safety of healthcare services, becomes of crucial importance in both public and private hospitals in Italy. In such context, education and training of risk managers should be multi disciplinary, ad hoc designed on recent regulations, and, more in general, help to build a new era in healthcare management.